Pengembangan Digital Entrepreneurship bagi Siswa SMK Buddhi Dharma untuk Meningkatkan Daya Saing dan Kesiapan Kerja - Tri Angreni; Georgius Listen; Pujiarti Pujiarti; Sutrisna Sutrisna; Yopie Chandra (Jurnal Pengabdian Masyarakat, 2026)
This community service activity aims to develop digital entrepreneurship of Buddhi Dharma Vocational School students to increase competitiveness and work readiness. The background of the activity is based on the low understanding and skills of students in utilizing digital technology as a means of entrepreneurship. The method used is practice-based training consisting of socialization, training, and hands-on practice stages. The participants of the activity were students of levels XI and XII who were given material related to the concept of digital entrepreneurship, social media-based marketing strategies, and the use of e-commerce platforms. The results of the activity showed an increase in students' understanding of digital entrepreneurship which was shown through a comparison of pre-test and post-test. In addition, students are able to design simple business ideas, create accounts on digital platforms, and compile product marketing content. Improvements are also seen in the aspects of students' confidence and communication skills in presenting business ideas. The active involvement of participants during the activity showed that practice-based training methods were effective in improving competence. This program provides a learning experience that is applicable and relevant to the needs of the world of work. Therefore, similar activities need to be carried out on an ongoing basis through collaboration between schools and universities to support the formation of adaptive and independent graduates in the digital era.